PEMANFAATAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA MENGENAI CIRI CIRI PUBERTAS DI KELAS 6 SD NEGERI TONJONG 05 - Mukti Wibowo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kuningan, 2023)
ABSTRAK Setelah dilaksanakan penelitian mengenai pemanfaatan media pop-up book terhadap peningkatan hasil belajar siswa aktifitas guru dan aktifitas siswa yang dilaksanakan di kelas VI SD tonjong 05.tahun ajaran 2022/2023 menegenai ciri ciri pubertas Hasilnya menunjukan bahwa aktifitas siswa pada ketiga komponen pembelajaran terjadi peningkatan yang cukup signifikanhasil belajar siklus 1 (25%) suklus 2 (87%,), aktifitas siswa siklus 1 (66,3%) dan siklus 2 (87,5% serta aktifitas guru silus 1 (70% ) dan siklus 2 (96%) Kata kunci: Pop-up Book. Pubertas. USE OF POP-UP BOOK MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES REGARDING THE CHARACTERISTICS OF PUBERTY IN CLASS 6 OF TONJONG NEGERI PRIMARY SCHOOL 05 ABSTRACT After conducting research regarding the use of pop-up book media to improve student learning outcomes, teacher activities and student activities carried out in class VI of SD Tonjong 05. 2022/2023 academic year regarding the characteristics of puberty. The results show that student activity in the three learning components has increased significantly. quite significant learning outcomes for cycle 1 (25%) for cycle 2 (87%), student activities for cycle 1 (66.3%) and cycle 2 (87.5%) and teacher activities for cycle 1 (70%) and cycle 2 (96% ) Keywords: Pop-up Book. Puberty